Patient satisfaction with HIV/AIDS care and treatment in the decentralization of services delivery in Vietnam. - Bach Xuan Tran (PLoS ONE, 2012)
OBJECTIVE: We evaluated the patient satisfaction with HIV/AIDS care and treatment and its determinants across levels of health service administration in Vietnam. METHODS: We interviewed 1016 patients at 7 hospitals and health centers in three epicenters, including Hanoi, Hai Phong, and Ho Chi Minh City. The Satisfaction with HIV/AIDS Treatment Interview Scale (SATIS) was developed, and 3 dimensions were constructed using factor analysis, namely "Quality and Convenience"; "Availability and Responsiveness"; and "Competence of health care workers". RESULTS: In a band score of (0; 10), the mean scores of all domains were large; it was the highest in "Competence of health workers" (9.34±0.84), and the lowest in "Quality and Convenience" (9.03±1.04). The percentages of respondents completely satisfied with overall service quality and treatment outcomes were 42.4% and 18.8%, respectively. In multivariate analysis, factors related to higher satisfaction included female sex, older age, and living with spouses or partners. Meanwhile, lower satisfaction was found among patients who were attending provincial and district clinics; in the richest group; had higher CD4 count; and drug users. CONCLUSION: This study highlights the importance of improving the quality of HIV/AIDS services at the provincial and district clinics. Potential strategies include capacity building for health workers, integrative service delivery, engagements of family members in treatment supports, and additional attention and comprehensive care for drug users with HIV/AIDS.